The Effect of Store Atmosphere Shopping Lifestyle and Fashion Involvement on The Purchase Decision of Uniqlo Products in Mataram - Nurul Sakinah; Menik Aryani; Lu`luin Najwa (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
This study aims to determine the effect of Store Atmosphere, Shopping Lifestyle, and Fashion Involvement on Purchase Decisions for Uniqlo Products in Mataram City. This study uses a quantitative approach with a sample size of 96 respondents. Data collection was carried out through a questionnaire using a Likert scale as a measuring tool, and data analysis using multiple regression with the help of SPSS version 30. The results of this study found that: 1 Store Atmosphere (X1), has a partial effect on purchasing decisions for Uniqlo products in Mataram City. 2 Shopping Lifestyle has a partial effect on purchasing decisions for Uniqlo products in Mataram City. Fashion Involvement has a partial effect on purchasing decisions for Uniqlo products in Mataram City. Store Atmosphere, Shopping Lifestyle, and Fashion Involvement have a simultaneous (together) effect on purchasing decisions for Uniqlo products in Mataram City.Keywords: Store Atmopshere, Shopping Lifestyle, Fashion Involvement, Purchase Decision.